Manganese carbonate nanoparticles‐mediated mitochondrial dysfunction for enhanced sonodynamic therapy. Issue 2 (30th September 2021) - Zhang, Haoyuan; Pan, Xueting; Wu, Qingyuan; Guo, Juan; Wang, Chaohui; Liu, Huiyu
Abstract: Sonodynamic therapy (SDT) has attracted widespread attention due to its non‐invasiveness and deep tissue penetration. However, the development of efficient sonodynamic nanoplatforms to improve the therapeutic efficiency is still one of the main challenges of current research. In this work, a new type of sonosensitizer prepared by a simple method, manganese carbonate nanoparticles (MnCO3 NPs), is used for enhanced SDT. MnCO3 NPs could generate large amounts of 1 O2 and OH under ultrasound irradiation. At the same time, CO2 and Mn ions could be released in a weak acid environment due to the excellent degradability of MnCO3 NPs. The CO2 bubbles caused cell necrosis by ultrasonic cavitation and used for ultrasound imaging. And Mn ions activated the mitochondrial cell apoptosis pathway. In vivo experiments proved that this sonosensitizer with mitochondrial regulatory capacity showed high tumor inhibition rates for enhanced sonodynamic tumor therapy. Abstract : The cubic manganese carbonate nanoparticles (MnCO3 NPs) are prepared by a simple synthesis method for enhanced sonodynamic therapy. It is proved that the high sonodynamic performance of MnCO3 NPs is related to its band gap. The CO2 and Mn ions produced by the degradation can achieve ultrasonic cavitation and activate the mitochondrial cell apoptosis pathway, respectively. This work provides a new avenue for the development of nanotheranostics.